A NEW FRAMEWORK IN CREDIT ALLOCATION: BLOCKCHAIN AND KYC INTEGRATION - Rahma Bamasdoos; Dr. Mohammed Jameel Hashmi; Dr.L.K Suresh Kumar (The Bioscan, 2024)
The peer-to-peer variant of digital currency will enable any financial institution seeking regulatory compliance to first under-take a Know Your Customer (KYC) procedure. Blockchain technology has emerged as a new method to enhance the effi-ciency of the KYC procedure. It offers robust protection against fraudulent activities by ensuring that the KYC process is transparent, secure, and immutable. Blockchain technology has received global acknowledgment for its potential to revolu-tionize the KYC process. Financial institutions may readily access customer information held on a decentralized network enabled by blockchain technology. Ethereum blockchain technology may enhance the efficiency of financial institutions by significantly reducing the time and costs associated with KYC processes. The objective of this research is to provide a viable and enduring solution to the issues at hand. The proposed strategy entails the central bank maintaining a comprehensive registry of all registered banks and meticulously monitoring their adherence to existing regulations on customer acquisition and KYC compliance.